2019
DOI: 10.1136/bmjopen-2019-029058
|View full text |Cite
|
Sign up to set email alerts
|

Initiation and completion rates of isoniazid preventive therapy among people living with HIV in Far-Western Region of Nepal: a retrospective cohort study

Abstract: ObjectivesIsoniazid preventive therapy (IPT), for people living with HIV (PLHIV) is the proven and recommended intervention to avert tuberculosis (TB). In 2015, Nepal implemented 6 months of IPT for all PLHIV registered for HIV care in antiretroviral therapy (ART) centres. After programmatic implementation, there has been no systematic assessment of IPT initiation and completion rates among PLHIV. We aimed to assess IPT initiation and completion rates in the Far-Western Region (FWR) of Nepal.DesignWe conducted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 25 publications
3
13
1
Order By: Relevance
“…Although several factors such as socioeconomic factors, regimen complexity, long duration of treatment, and pattern of health care delivery system are known to affect adherence to TB drugs, the extent to which additional factor affects TB adherence needs to be explored ( WHO, 2003 ). Past studies evaluating the adherence either focused on highly specific patient population, for instance, those with acquired immune deficiency syndrome ( Shayo et al, 2015 ; Dhungana et al, 2019 ), or based on local registry data with limited sample size and lack of medical history of the individual patient ( Mok et al, 2018 ). Therefore, we sought to assess the adherence to TB drugs and factors affecting adherence among TB patients in South Korea by using a nationwide claims database from 2017 to 2018.…”
Section: Introductionmentioning
confidence: 99%
“…Although several factors such as socioeconomic factors, regimen complexity, long duration of treatment, and pattern of health care delivery system are known to affect adherence to TB drugs, the extent to which additional factor affects TB adherence needs to be explored ( WHO, 2003 ). Past studies evaluating the adherence either focused on highly specific patient population, for instance, those with acquired immune deficiency syndrome ( Shayo et al, 2015 ; Dhungana et al, 2019 ), or based on local registry data with limited sample size and lack of medical history of the individual patient ( Mok et al, 2018 ). Therefore, we sought to assess the adherence to TB drugs and factors affecting adherence among TB patients in South Korea by using a nationwide claims database from 2017 to 2018.…”
Section: Introductionmentioning
confidence: 99%
“…WHO recommends the completion of at least six months IPT for the successful prevention of active tuberculosis among PLHIV (4,10). Globally, six-month IPT completion has been reported to range from 39-99% (28)(29)(30)(31)(32)(33)(34)(35)(36)(37), and in Tanzania studies reported 65%-98% of those who initiated IPT, completed the six month treatment course (6,20,(38)(39)(40). Most epidemiological studies have shown that IPT completion reduces the risks of mortality among PLHIV (8,26,41)…”
Section: Introductionmentioning
confidence: 99%
“…Visits corresponding to being in care for more than one year had higher odds of IPT initiation than earlier visits. IPT initiation later after HIV care enrolment is also reported in Nepal (24). Lower IPT initiation associated with Iringa compared to Dar es Salaam and Njombe explains dynamics in IPT implementation which also differs from health facility to health facility as reported in another study (24).…”
Section: Study Population and Data Collectionmentioning
confidence: 61%
“…IPT initiation later after HIV care enrolment is also reported in Nepal (24). Lower IPT initiation associated with Iringa compared to Dar es Salaam and Njombe explains dynamics in IPT implementation which also differs from health facility to health facility as reported in another study (24). Lower IPT initiation in visits with good adherence is contrary to what is expected in normal program settings as good ARV adherence was one of the criteria for IPT initiation.…”
Section: Study Population and Data Collectionmentioning
confidence: 75%